Evaluation of an intervention to train health professionals working with Aboriginal and Torres Strait Islander people to provide smoking cessation advice. (20th February 2019) - Martin, Kimberley; Dono, Joanne; Stewart, Harold (Bundamurra); Sparrow, Alana; Miller, Caroline; Roder, David; Bowden, Jacqueline
Abstract: Objective : To investigate the effectiveness and cultural relevance of Quitskills training tailored for health professionals working with Aboriginal and Torres Strait Islander people who smoke. Methods : A retrospective analysis was conducted with data collected from 860 participants (54% Aboriginal and Torres Strait Islander participants) in tailored Quitskills training from 2012 to 2016. Course participants took part in a survey at pre‐training, post‐training and four‐six weeks post‐training to assess confidence in skills to address tobacco, and perceptions of the strengths, areas for improvement and cultural relevance of the training. Results : Confidence in skills and knowledge to address tobacco increased significantly from pre‐ to post‐training (all indicators of confidence in skills increased p <0.001) and remained high at follow‐up. Tailored Quitskills training was perceived as being culturally relevant by Aboriginal and Torres Strait Islander participants, and the training facilitators were the most commonly cited strength of the training. Conclusions : Quitskills is an appropriate course for increasing skills and confidence among health professionals working with Aboriginal and Torres Strait Islander people who smoke. Implications for public health : Training courses that are tailored for Aboriginal and Torres Strait Islander people can build the capacity of the health workforce in a culturally relevant manner.